Methylmalonic acidemia in prenatal diagnosis - B.F. Zhou; C.X. Duan; D.L. Tang (IMR Press, 2020)
Objective: The objective of this study was to report the prenatal diagnosis for methylmalonic acidemia. Materials and Methods: Isolated methylmalonic acidemia was diagnosed by analyzing organic acids in the blood and urine. The specific subtype of methylmalonic acidemia was determined by molecular genetic testing. Prenatal diagnosis for methylmalonic acidemia includes ultrasound examination, conventional karyotyping using cultured amniocytes, chromosomal microarray analysis, and targeted sequencing using uncultured amniocytes. Results: We identified a novel mutation (NM_172250.2; c.491G>A) in the MMAA gene that might be associated with methylmalonic acidemia. The fetus and her father are both carriers of this mutation. Conclusion: A combination of prenatal ultrasound, conventional karyotyping, chromosomal microarray analysis, and target sequencing will provide a more accurate risk assessment for methylmalonic acidemia.